Implementasi Kebijakan Pemberian Tunjangan Kinerja (Studi pada ASN Lingkup Pemerintah Kabupaten Tulungagung) - Linda Kurniawati; Abu Talkah; Ahsin Daroini (Otonomi, 2022)
The government issued a national policy in the form of Presidential Regulation 81/2010 concerning Grand Design Reform 2010-2025. This is the benchmarks for the success of the implementation of bureaucratic reform. The purpose of providing Performance Allowance is as an effort by the Government to provide performance motivation and improve welfare for employees. The policy that regulates the provision of employee performance allowances for civil servants is contained in Tulungagung Regent Regulation Number 3/2021. The aspects underlying the provision of employee performance allowances are aspects of work discipline and aspects of work productivity. From the main problems presented, the purpose of this study is to analyze the implementation of policies on the provision of employee performance allowances. The researcher uses Ripley and Franklin's theory about the determinants of success in policy implementation. The results of this study indicate that the policy does not have a significant impact in the discipline aspect, it can be seen from the many employees who take disciplinary actions, from the aspect of work productivity there are still many employees who do not have high competence and integrity in the assigned tasks. However, it has a positive impact in terms of improving the welfare of employees.